Early ripening soybean variety Avantiuryn - Білявська, Л. Г.; Васецький, Ю. П.; Білявський, Ю. В.; Діянова, А. О. (Scientific Progress & Innovations, 2018)
Soybean, its uses, genetic potential, customer and processer requirements are considered in the study. Growth of soybean demand has been stated. Ways of increasing soybean output in Ukraine in accordance with climatic zones of Ukraine are defined. Thereafter, ways and perspectives of formation of soybean variety resources in the country are considered. A great number of various soybean varieties, most of which with narrow environmental and geographical adaptation have been recorded into the State Register of plant varieties adaptable to distribution in Ukraine. According to the modern requirements soybean variety has to be high-yield, adaptive, possess high genetic potential and appropriate degree of resistance to biotic and abiotic environmental factors as well. The part of early ripening high-yielding soybean varieties has been growing. This crop is an excellent preceding crop for winter wheat. Nowadays the variety is a mean of yield growth as well as a factor of increasing economic efficiency of production. The main research objective was to select early ripening and high-yield soybean varieties for all zones of Ukraine with high processability degree, the duration of vegetation period of 80–95 days, seed yield of 3.0–4.0 t/hа, protein content of 40–43 % and fat content of 22–26 % as well. In order to select and introduce the varieties in Poltava, Kharkiv, Sumy and Dnipropetrovs’k regions sources of adaptability to limiting factors (by hybridization) have been used with the aim to estimate drought-resistance, disease resistance, resistance to acid soil and complex of climatic factors as well. Field and laboratory-field experiments, phenological observations have been carried out in accordance with the State Standards of Ukraine and methodical recommendations of the state variety trial. Morphological and biological characteristics during the vegetation period have been described according to the unified classifier of the kind Glycine. Early ripening variety with increased basic potential has been selected by the method of hybridization of adaptability sources to stress environmental factors on the basis of many years' practical experience in the soybean selection field. Avantiuryn variety has been recorded into the State Register of plant varieties adaptable to distribution in Ukraine. Some requirements to the agrotechnics elements have been given. Plant height is 71–90 centimeters. Height of attachment of bottom bean is 12–15 сm. Weight of 1000 seeds is 180–200 grams. Protein content of seed is 38 %, fat content is 22 %. Potential grain yield in the conditions of Ukraine is 3.0–3.5 t/hа. The variety is characterized by increased adaptability to unfavourable growing conditions including growing on acid soil (pH 4.5–5.5). The variety grown for grain production is resistant to lodging and bean splitting. The variety is resistant to bacterial and virus diseases and slightly damaged by pests. Agrotechnics of Avantiuryn variety is standard. Seeding rate is 550–650 thousand germinable seeds per one hectare. The variety is well responsive to fertilization and presowing seed inoculation with biological preparations. This variety is recommended to be grown for grain production in Steppe and Forest-Steppe of Ukraine. Size equality of seed is 95 %.